A Psychological Review of Repetitive Handwashing Behavior in Obsessive-Compulsive Disorder (OCD) - Zein, Annisa Elya; Firyal, Atsilah; Zaidhan, Emilia; Rohmawati, Desy; Hoirunnurmalasari, Hoirunnurmalasari; Rahmi, Kus Hanna (PROMOTOR, 2024)
Obsessive-Compulsive Disorder (OCD) is a psychological condition characterized by intrusive obsessions and uncontrollable compulsions. One example of a common compulsive behavior associated with OCD is the habit of washing hands repeatedly. This journal discusses the psychological factors underlying the habit and its impact on the lives of individuals affected by OCD. Through literature analysis, we present insights into this phenomenon regarding OCD from a psychological perspective. This research uses a literature study method with a descriptive-analytical approach, collecting data from various sources relevant to the research topic. The limitation of this study is the limited number of recent sources and journals that discuss similar topics, it is hoped that in the future there will be many sources and psychology journals that discuss the topic of OCD, especially in the context of repetitive hand washing habits.